Question and Answers Forum

All Questions      Topic List

Limits Questions

Previous in All Question      Next in All Question      

Previous in Limits      Next in Limits      

Question Number 46330 by Saorey last updated on 24/Oct/18

pls help me!  L=lim_(x→1) (((x)^(1/(13)) −(x)^(1/7) )/((x)^(1/5) −(x)^(1/3) ))

$$\mathrm{pls}\:\mathrm{help}\:\mathrm{me}! \\ $$$$\mathrm{L}=\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\frac{\sqrt[{\mathrm{13}}]{\mathrm{x}}−\sqrt[{\mathrm{7}}]{\mathrm{x}}}{\sqrt[{\mathrm{5}}]{\mathrm{x}}−\sqrt[{\mathrm{3}}]{\mathrm{x}}} \\ $$

Commented by MJS last updated on 24/Oct/18

I would again recommend l′Hopital  lim_(x→1) ((x^a −x^b )/(x^c −x^d ))=lim_(x→1) (((d/dx)[x^a −x^b ])/((d/dx)[x^c −x^d ]))=lim_(x→1) ((ax^(a−1) −bx^(b−1) )/(cx^(c−1) −dx^(d−1) ))=  =lim_(x→1) ((ax^a −bx^b )/(cx^c −dx^d ))=((a−b)/(c−d))  with a=(1/(13)); b=(1/7); c=(1/5); d=(1/3)  L=((a−b)/(c−d))=(((1/(13))−(1/7))/((1/5)−(1/3)))=((−(6/(91)))/(−(2/(15))))=((45)/(91))

$$\mathrm{I}\:\mathrm{would}\:\mathrm{again}\:\mathrm{recommend}\:\mathrm{l}'\mathrm{Hopital} \\ $$$$\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\frac{{x}^{{a}} −{x}^{{b}} }{{x}^{{c}} −{x}^{{d}} }=\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\frac{\frac{{d}}{{dx}}\left[{x}^{{a}} −{x}^{{b}} \right]}{\frac{{d}}{{dx}}\left[{x}^{{c}} −{x}^{{d}} \right]}=\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\frac{{ax}^{{a}−\mathrm{1}} −{bx}^{{b}−\mathrm{1}} }{{cx}^{{c}−\mathrm{1}} −{dx}^{{d}−\mathrm{1}} }= \\ $$$$=\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\frac{{ax}^{{a}} −{bx}^{{b}} }{{cx}^{{c}} −{dx}^{{d}} }=\frac{{a}−{b}}{{c}−{d}} \\ $$$$\mathrm{with}\:{a}=\frac{\mathrm{1}}{\mathrm{13}};\:{b}=\frac{\mathrm{1}}{\mathrm{7}};\:{c}=\frac{\mathrm{1}}{\mathrm{5}};\:{d}=\frac{\mathrm{1}}{\mathrm{3}} \\ $$$${L}=\frac{{a}−{b}}{{c}−{d}}=\frac{\frac{\mathrm{1}}{\mathrm{13}}−\frac{\mathrm{1}}{\mathrm{7}}}{\frac{\mathrm{1}}{\mathrm{5}}−\frac{\mathrm{1}}{\mathrm{3}}}=\frac{−\frac{\mathrm{6}}{\mathrm{91}}}{−\frac{\mathrm{2}}{\mathrm{15}}}=\frac{\mathrm{45}}{\mathrm{91}} \\ $$

Commented by hassentimol last updated on 24/Oct/18

What is L′Hopital, please sir ?

$${What}\:{is}\:{L}'{Hopital},\:{please}\:{sir}\:? \\ $$$$ \\ $$

Commented by MJS last updated on 24/Oct/18

lim_(x→a)  ((f(x))/(g(x)))=lim_(x→a)  ((f′(x))/(g′(x))) if f(a)=0 and g(a)=0 xor  f(a)=±∞ and g(a)=±∞  example  lim_(x→0)  (xln x) =lim_(x→0)  ((ln x)/x^(−1) ) =lim_(x→0)  (((d/dx)[ln x])/((d/dx)[x^(−1) ]))=  =lim_(x→0)  (x^(−1) /(−x^(−2) )) =lim_(x→0)  −x =0

$$\underset{{x}\rightarrow{a}} {\mathrm{lim}}\:\frac{{f}\left({x}\right)}{{g}\left({x}\right)}=\underset{{x}\rightarrow{a}} {\mathrm{lim}}\:\frac{{f}'\left({x}\right)}{{g}'\left({x}\right)}\:\mathrm{if}\:{f}\left({a}\right)=\mathrm{0}\:\mathrm{and}\:{g}\left({a}\right)=\mathrm{0}\:\mathrm{xor} \\ $$$${f}\left({a}\right)=\pm\infty\:\mathrm{and}\:{g}\left({a}\right)=\pm\infty \\ $$$$\mathrm{example} \\ $$$$\underset{{x}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\left({x}\mathrm{ln}\:{x}\right)\:=\underset{{x}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\mathrm{ln}\:{x}}{{x}^{−\mathrm{1}} }\:=\underset{{x}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\frac{{d}}{{dx}}\left[\mathrm{ln}\:{x}\right]}{\frac{{d}}{{dx}}\left[{x}^{−\mathrm{1}} \right]}= \\ $$$$=\underset{{x}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{{x}^{−\mathrm{1}} }{−{x}^{−\mathrm{2}} }\:=\underset{{x}\rightarrow\mathrm{0}} {\mathrm{lim}}\:−{x}\:=\mathrm{0} \\ $$

Answered by ajfour last updated on 24/Oct/18

L = lim_(h→0) (((1+h)^(1/13) −(1+h)^(1/7) )/((1+h)^(1/5) −(1+h)^(1/3) ))      =lim_(h→0) ((1+(h/(13))+...−1−(h/7)−...)/(1+(h/5)+...−1−(h/3)−...))      = ((−6/91)/(−2/15)) = ((45)/(91)) .

$${L}\:=\:\underset{{h}\rightarrow\mathrm{0}} {\mathrm{lim}}\frac{\left(\mathrm{1}+{h}\right)^{\mathrm{1}/\mathrm{13}} −\left(\mathrm{1}+{h}\right)^{\mathrm{1}/\mathrm{7}} }{\left(\mathrm{1}+{h}\right)^{\mathrm{1}/\mathrm{5}} −\left(\mathrm{1}+{h}\right)^{\mathrm{1}/\mathrm{3}} } \\ $$$$\:\:\:\:=\underset{{h}\rightarrow\mathrm{0}} {\mathrm{lim}}\frac{\mathrm{1}+\frac{{h}}{\mathrm{13}}+...−\mathrm{1}−\frac{{h}}{\mathrm{7}}−...}{\mathrm{1}+\frac{{h}}{\mathrm{5}}+...−\mathrm{1}−\frac{{h}}{\mathrm{3}}−...} \\ $$$$\:\:\:\:=\:\frac{−\mathrm{6}/\mathrm{91}}{−\mathrm{2}/\mathrm{15}}\:=\:\frac{\mathrm{45}}{\mathrm{91}}\:. \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com